2007
DOI: 10.4049/jimmunol.178.8.5253
|View full text |Cite
|
Sign up to set email alerts
|

Free Cholesterol Alters Lipid Raft Structure and Function Regulating Neutrophil Ca2+ Entry and Respiratory Burst: Correlations with Calcium Channel Raft Trafficking

Abstract: Recent studies associate cholesterol excess and atherosclerosis with inflammation. The link between these processes is not understood, but cholesterol is an important component of lipid rafts. Rafts are thought to concentrate membrane signaling molecules and thus regulate cell signaling through G protein-coupled pathways. We used methyl β-cyclodextrin to deplete cholesterol from polymorphonuclear neutrophil (PMN) rafts and thus study the effects of raft disruption on G protein-coupled Ca2+ mobilization. Methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 52 publications
6
44
0
Order By: Relevance
“…We have also shown that TRPC1 was predominantly localized in lipid microdomains in C2C12 myoblasts, as previously reported in other cell types (Murata et al, 2007;Kannan et al, 2007). Current evidence suggests that lipid microdomains, dynamic plasma membrane structures enriched in cholesterol and sphingolipids, concentrate and segregate several membrane signalling proteins and serve as scaffolds for activation of Ca 2+ -dependent mechanisms (Ambudkar, 2006).…”
Section: Journal Of Cell Science 122 (9)supporting
confidence: 62%
See 1 more Smart Citation
“…We have also shown that TRPC1 was predominantly localized in lipid microdomains in C2C12 myoblasts, as previously reported in other cell types (Murata et al, 2007;Kannan et al, 2007). Current evidence suggests that lipid microdomains, dynamic plasma membrane structures enriched in cholesterol and sphingolipids, concentrate and segregate several membrane signalling proteins and serve as scaffolds for activation of Ca 2+ -dependent mechanisms (Ambudkar, 2006).…”
Section: Journal Of Cell Science 122 (9)supporting
confidence: 62%
“…As TRPC-based channels may be associated with highly structured cholesterol-enriched lipid-microdomains (Lockwich et al, 2000;Murata et al, 2007;Kannan et al, 2007), we next searched for TRPC1 localization in lipid microdomains and the possible functional repercussion on the channel activity in C2C12 myoblasts. To this purpose, we used centrifugation to equilibrium on discontinuous sucrose density gradients to isolate lipid rafts, which were then analyzed by western blotting for the presence of the typical marker protein caveolin 1 (Cav1) (Fig.…”
Section: Functional Localization Of Trpc1 In Lipid Microdomains In Skmentioning
confidence: 99%
“…Similar to cholesterol depletion, sequestration of cholesterol (and thus disruption of its organization) within the membrane, using filipin, influences activation of CD18 integrins leading to impaired T-cell adhesion (32). In this fashion, changes in membrane cholesterol have been shown to interfere with signaling related to lipid rafts, which provide spatial organization for select transmembrane proteins and act as signaling platforms responsible for coordinating outside-in and inside-out signal transduction (21,32,49). Interestingly, these cholesterolrich microdomains have also been implicated as mechanotransduction centers such as caveolae, a subtype of lipid rafts that play a role in the mechanotransduction of shear stress and pressure by endothelial cells (41,43,44).…”
mentioning
confidence: 99%
“…63 At very low concentrations, free cholesterol can alter Ca 2+ entry via TRPC1, in cholesterol depleted polymorphonuclear neutrophils. 64 It has been observed that TRPC1 redistributes into the raft fractions in response to cholesterol. Localization of TRPC1 in the lipid raft in response to ketocholesterol has been observed in THP-1 monocytic cells.…”
Section: Meeting Reportmentioning
confidence: 99%
“…57,58 A number of studies have indicated that TRP channels are also localized in specific regions of the plasma membrane microdomain commonly known as lipid rafts that scaffold several other signaling complexes. 47,[63][64][65] For example, TRPM7 in vascular smooth muscle cells is localized in the fraction that corresponds to the caveolae fraction. Immunofluorescence analysis also confirms that TRPM7 co-localizes with flotillin-2, a marker of lipid rafts.…”
Section: Meeting Reportmentioning
confidence: 99%